Decomposition Analysis on the Air Pollutant Baseline Emission Factors in China's Power Sector. (May 2017) - Shen, Shudong; Wang, Can
Abstract: Air pollution is one of the major problem in China's power sector. This paper calculates the baseline emission factor in the power sector and uses the index decomposition method to analyze the variation trend of the emission factor. For the SO2, the simple average baseline emission factor is 1.15 kg/MWh. The east China has the highest emission factor and the central has the lowest number. As for the NOx, the simple average is 1.76 kg/MWh, the northeast China has the highest emission factor, and the South China has the lowest emission factor. And the decomposition analysis takes into account three driving factors: pollution control technology level, fuel mix and power structure. The variation from 2005 to 2013 of the SO2 baseline emission factor is mostly influenced by the pollutant control technology improvement, and fuel mix in thermal power industry makes small contribution on the emission reduction and the influence brought by fuel mix varies a lot among different regions. As for the variation of NOx emission factor from 2007 to 2013, the technology level causes biggest variation too. The fuel mix also makes some positive contribution on east and central China. And the power structure don't have significant influence on the variation of both SO2 and NOx baseline emission factor.